Multicenter Registry Using Propensity Score Analysis to Compare a Novel Transport/Preservation System to Traditional Means on Postoperative Hospital Outcomes and Costs for Heart Transplant Patients. Issue 4 (18th November 2022) - Voigt, Jeffrey D.; Leacche, Marzia; Copeland, Hannah; Wolfe, Stanley B.; Pham, Si M.; Shudo, Yasuhiro; Molina, Ezequiel; Jacobs, Jeffrey P.; Stukov, Yuriy; Meyer, Dan; Philpott, Jonathan; Kawabori, Masashi; et al.
Abstract : The standard method for cardiac allograft preservation for the past 50 years has been static storage using crushed ice. A heart transplant transportation system designed to improve preservation quality with temperature monitoring, the Paragonix SherpaPak Cardiac Transport System (SCTS), was evaluated for its impact on postoperative costs relative to conventional ice storage. Observational US multicenter registry data collected during the August 2015 to November 2021 timeframe from 12 transplant hospitals were analyzed using logistic regression analysis and propensity matching to balance measured baseline covariates and to reduce selection bias. Hospital cost and outcome data post-transplant were then evaluated using various statistical methods. One hundred seventy-four (174) patients were identified resulting in 87 matches. Baseline characteristics were similar between groups. The SCTS group had a significantly lower proportion of ICU days on post-transplant mechanical circulatory support ( p < 0.0001); significantly fewer patients on extracorporeal membrane oxygenation ( p = 0.017); and significantly fewer patients experiencing severe primary graft dysfunction (PGD) ( p = 0.03). Overall hospital plus mechanical circulatory support post-transplant costs were significantly lower by $26.7K in the CTS cohort ( p = 0.03). Use of the SCTS is associated with improved clinical outcomes resulting in significantly lower overall hospital care costs.